2021
DOI: 10.1101/2021.02.07.21251311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust immune responses after one dose of BNT162b2 mRNA vaccine dose in SARS-CoV-2 experienced individuals

Abstract: The advent of COVID-19 vaccines will play a major role in helping to end the pandemic that has killed millions worldwide. Vaccine candidates have demonstrated robust humoral responses and have protected against infection. However, efficacy trials were focused on individuals with no prior exposure to SARS-CoV-2, and, as a result, little is known about immune responses induced by these mRNA vaccines in individuals who recovered from COVID-19. Here, we evaluated immune responses in 32 subjects who received two-do… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
61
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 80 publications
17
61
0
Order By: Relevance
“…Overall, these data also add to our understanding of SARS-CoV2 mRNA vaccine-induced immune responses in several ways. First, our serological data is consistent with several other recent studies 9,10,12,13,16,17 indicating robust boosting of antibody responses in SARS-CoV2 recovered subjects after the first vaccine dose, but little benefit to antibody titers after the second vaccine dose. Moreover, we identified a similar effect for virus-specific memory B cells, demonstrating that both a quantitative and qualitative plateau in vaccine-induced memory B cells is achieved following the first dose of vaccine with little additional change to the memory B cell response following booster vaccination.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, these data also add to our understanding of SARS-CoV2 mRNA vaccine-induced immune responses in several ways. First, our serological data is consistent with several other recent studies 9,10,12,13,16,17 indicating robust boosting of antibody responses in SARS-CoV2 recovered subjects after the first vaccine dose, but little benefit to antibody titers after the second vaccine dose. Moreover, we identified a similar effect for virus-specific memory B cells, demonstrating that both a quantitative and qualitative plateau in vaccine-induced memory B cells is achieved following the first dose of vaccine with little additional change to the memory B cell response following booster vaccination.…”
Section: Discussionsupporting
confidence: 92%
“…As these individuals have already generated a primary immune response to SARS-CoV2 during their natural infection, it is possible that a single dose of vaccine could be enough to sufficiently boost their antibody and memory B cell responses. Indeed, several recent studies have indicated that antibody responses can be robustly induced in SARS-CoV2 experienced individuals, consistent with an anamnestic response 912 . Although one study suggests that memory B cells might also be boosted after a single vaccine dose 13 , it remains unclear how well memory B cell responses are induced in SARS-CoV2 naïve versus SARS-CoV2 experienced subjects after one versus two doses of mRNA vaccine.…”
Section: Introductionmentioning
confidence: 64%
“…More antigen being presented to the immune system does not always equate to higher immunogenicity markers, which appears to be the case between 10 and 30 ug dosing. This is also seen in COVID-19 recovered patients who increase their VNT50 and antibody titres after one dose of vaccination, but not after the second 23 (23). It is also seen in AstraZeneca’s trial data where a low dosing regimen led to equivalent if not greater efficacy than standard dosing 24 (24).…”
Section: Discussionmentioning
confidence: 65%
“… 9 In the New York City cohort, direct ELISA was used to quantify antibody titres on serum as previously described. 10 Titre of 5000 units or greater was used as the cut-off to determine an adequate response to vaccination. IgG antibodies against the S1 domain of the spike protein of SARS-CoV-2 were tested in Erlangen participants using the commercial ELISA from Euroimmun (Lübeck, Germany) on the EUROIMMUN Analyzer I platform and according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%